2019
DOI: 10.1111/bcp.13846
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dosing regimens of isoniazid and rifampicin in children with tuberculosis in India

Abstract: Aims Pharmacokinetic studies in the past have shown inadequate antituberculosis drug levels in children with the currently available dosing regimens. This study attempted to investigate the pharmacokinetics of isoniazid and rifampicin, when used in children, and to optimize their dosing regimens. Methods Data were collected from 41 children, aged 2–16 years, who were being treated with antituberculosis drugs for at least 2 months. Concentration measurements were done for 6 h and analysed using a nonlinear, mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
(46 reference statements)
2
12
0
Order By: Relevance
“…Simulations of optimal doses demonstrated that 10 mg/kg/day of isoniazid, which is the currently recommended WHO dose, was adequate to maintain steady-state plasma and CSF exposures above the EC 50 with PTA >90% in both fast and slow acetylators. Similar results were reported in a previous study by Aruldhas et al, who studied pulmonary and lymph node TB in Indian children aged 2 to 16 years ( 19 ). However, a study by Zvada et al showed that the dose of 10 mg/kg/day resulted in inadequate exposure in intermediate and fast acetylators ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Simulations of optimal doses demonstrated that 10 mg/kg/day of isoniazid, which is the currently recommended WHO dose, was adequate to maintain steady-state plasma and CSF exposures above the EC 50 with PTA >90% in both fast and slow acetylators. Similar results were reported in a previous study by Aruldhas et al, who studied pulmonary and lymph node TB in Indian children aged 2 to 16 years ( 19 ). However, a study by Zvada et al showed that the dose of 10 mg/kg/day resulted in inadequate exposure in intermediate and fast acetylators ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…Due to those findings, current pediatric dose recommendations from the WHO in 2014 have been increased, i.e., isoniazid 10 mg/kg, rifampin 15 mg/kg, pyrazinamide 35 mg/kg, and ethambutol 20 mg/kg daily ( 14 ). Still, this increased dosing has been shown to fail to achieve therapeutic drug concentrations in certain pediatric studies ( 18 20 ).…”
Section: Textmentioning
confidence: 99%
“…(Chan et al, 2017) Singaporean Chinese were found to be predominantly fast acetylators (75%), while Singaporean Indians were primarily slow acetylators (62.5%). (Aruldhas et al, 2019) At the current World Health Organisation (WHO) recommended pediatric doses, the simulated target attainment of the therapeutic peak INH concentrations (Cmax > 3 mg ml À1 ), and amount of exposure (AUC 0-24 > 10.5 mg x h ml À1 ) are close to !90% in both fast and slow acetylators. (Aruldhas et al, 2019) This suggests that the low-level INH resistance may not correspond to clinical resistance, as sufficient drug concentrations are still attained in vivo, and hence, high-dose INH is not required.…”
Section: Discussionmentioning
confidence: 94%
“…(Rieder and Van Deun, 2017;Katiyar et al, 2008;Jacobson et al, 2011;Xu et al, 2017) However, at the current World Health Organisation (WHO) recommended doses for pediatrics at 10 -15 mg/kg/day, isoniazid concentrations to overcome the phenotype of decreased drug susceptibility may already be readily obtained in-vivo. (Aruldhas et al, 2019;Rangari et al, 2015) INH metabolism is dependent on the genotype of the N-acetyltransferase (NAT) enzyme, explaining the large variability in its clearance. Fast acetylators are generally at risk of drug underexposure, and a Singapore-based study found that close to 64% of the cohort were fast acetylators, with variation in ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, when rifampicin 35-40 mg/kg was administered to children weighing 6-30 kg, 74.2% had a Cmax greater than 8 μg/mL. 27) In a pediatric study, children with low blood levels of rifampicin were more likely to have…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%